Allergic airway inflammation induces a pro-secretory epithelial ion transport phenotype in mice - Anagnostopoulou, Pinelopi; Dai, L.; Schatterny, Jolanthe; Hirtz, Stephanie; Dürr, Julia; Mall, Marcus A. (The European respiratory journal, 2010)
The airway epithelium is a central effector tissue in allergic inflammation and T-helper cell (Th) type 2-driven epithelial responses, such as mucus hypersecretion contribute to airflow obstruction in allergic airway disease. Previous in vitro studies demonstrated that Th2 cytokines also act as potent modulators of epithelial ion transport and fluid secretion, but the in vivo effect of allergic inflammation on airway ion transport remains unknown. - We, therefore, induced allergic inflammation by intratracheal instillation of Aspergillus fumigatus extract or interleukin-13 in mice and determined effects on ion transport in native tracheal and bronchial tissues. - We demonstrate that allergic inflammation enhanced basal Cl- secretion in both airway regions and inhibited epithelial Na+ channel (ENaC)-mediated Na+ absorption and increased Ca2+-dependent Cl- secretion in bronchi. Allergen-induced alterations in bronchial ion transport were associated with reduced transcript levels of α-, β- and γENaC, and were largely abrogated in signal transducer and activator of transcription (Stat)6-/- mice. - Our studies demonstrate that Th2-dependent airway inflammation produced a pro-secretory ion transport phenotype in vivo, which was largely Stat6-dependent. These results suggest that Th2-mediated fluid secretion may improve airway surface hydration and clearance of mucus that is hypersecreted in allergic airway diseases such as asthma, and identify epithelial Stat6 signalling as a potential therapeutic target to promote mucus hydration and airway clearance.
Gesehen am 22.11.2022